2020
DOI: 10.1186/s40634-020-00281-3
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment of a habitual patellar dislocation after a total knee arthroplasty with a closing-wedge distal femoral varus osteotomy and medial patello-femoral ligament reconstruction

Abstract: A 68-year-old female suffering from habitual patellar dislocations following a mal-positioned total knee arthroplasty (TKA) was successfully treated with a biplanar closed wedge distal femoral osteotomy (CWDFO) and medial patello-femoral ligament (MPFL) reconstruction. To the best of our knowledge, no such case has been previously described. Our experience with this case suggests that treatment for a patella dislocation following valgus mal-positioning of TKA should be considered positively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 14 publications
(15 reference statements)
0
6
0
Order By: Relevance
“…extensor mechanism reconstruction (as a.) only 16,32,12 All knees achieved normal patellar tracking Clinical and functional improvement with post-operative Knee Society Score of 92,85 and 79 none Shen et al 2020 [ 64 ] V 1 84 Patella maltracking after primary TKA Partial lateral patella facetectomy, lateral retinaculum release and vastus medialis restore 12 The knee achieved normal patellar tracking Clinical and functional improvement with post-operative Hospital for Special Surgery Clinical Score of 85 none Warschawski et al 2020 [ 65 ] IV 36 67 (49–78) Patella maltracking after primary TKA with one of more malrotated components Full-components revision 56 (5–145) All knees achieved normal patellar tracking, except one patient, had a recurrent dislocation episode Clinical and functional improvement with postoperative mean Knee Society Score of 86.2 at final follow-up 1 tibial tuberosity fracture Saito et al 2020 [ 66 ] V 1 68 Patella maltracking after primary TKA with femoral component installed at a valgus position Closing-wedge distal femoral varus osteotomy, MPFL reconstruction, lateral retinaculum release, patella resurfacing and substitution of the polyethylene insert 24 The knee achieved normal patellar tracking The Kujala functional score and the Oxford knee score improved from 24 to 58 and from 28 to 40 none * Patients were graded according to a knee rating system: 15 points were assigned for pain, 30 points for function, 10 points for deformity, and 10 points for motion. A score over 80 points represents a good result and over 90 points an excellent result …”
Section: Resultsmentioning
confidence: 99%
“…extensor mechanism reconstruction (as a.) only 16,32,12 All knees achieved normal patellar tracking Clinical and functional improvement with post-operative Knee Society Score of 92,85 and 79 none Shen et al 2020 [ 64 ] V 1 84 Patella maltracking after primary TKA Partial lateral patella facetectomy, lateral retinaculum release and vastus medialis restore 12 The knee achieved normal patellar tracking Clinical and functional improvement with post-operative Hospital for Special Surgery Clinical Score of 85 none Warschawski et al 2020 [ 65 ] IV 36 67 (49–78) Patella maltracking after primary TKA with one of more malrotated components Full-components revision 56 (5–145) All knees achieved normal patellar tracking, except one patient, had a recurrent dislocation episode Clinical and functional improvement with postoperative mean Knee Society Score of 86.2 at final follow-up 1 tibial tuberosity fracture Saito et al 2020 [ 66 ] V 1 68 Patella maltracking after primary TKA with femoral component installed at a valgus position Closing-wedge distal femoral varus osteotomy, MPFL reconstruction, lateral retinaculum release, patella resurfacing and substitution of the polyethylene insert 24 The knee achieved normal patellar tracking The Kujala functional score and the Oxford knee score improved from 24 to 58 and from 28 to 40 none * Patients were graded according to a knee rating system: 15 points were assigned for pain, 30 points for function, 10 points for deformity, and 10 points for motion. A score over 80 points represents a good result and over 90 points an excellent result …”
Section: Resultsmentioning
confidence: 99%
“…Eight case series included in our study concerned distal femoral osteotomy as an additional procedure to TKA [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ] ( Table 1 ). Five of them presented one-stage total knee arthroplasty with distal femoral osteotomy for the correction of extra-articular deformity with good results in the last follow-up (4 to 10 years of follow-up) [ 19 , 20 , 21 , 22 , 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…Five of them included post-traumatic patients with femoral fractures malunion (in total, 19 patients) [ 19 , 20 , 21 , 22 , 25 ]: constitutional in three patients, secondary after femoral osteotomy with overcorrection in three patients [ 22 ], and one with hypophosphatemic rickets [ 25 ]. Clinical and functional outcomes were shown in KSS [ 19 , 21 , 25 , 26 ], HSS [ 22 ], Kujala, and Oxford Knee Score [ 23 ], with significant increases at the last follow-up. Six studies also showed improvement in ROM post-surgery (range 85–107) [ 20 , 22 , 23 , 26 , 27 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations